2, 2′‐Biphenol‐based Ultrathin Microporous Nanofilms for Highly Efficient Molecular Sieving Separation. (17th October 2022) - Li, Shao‐Lu; Chang, Guoliang; Huang, Yangzheng; Kinooka, Ken; Chen, Yanting; Fu, Wenming; Gong, Genghao; Yoshioka, Tomohisa; McKeown, Neil B.; Hu, Yunxia
Abstract: Organic solvent nanofiltration (OSN) is an emerging membrane separation technology, which urgently requires robust, easily processed, OSN membranes possessing high permeance and small solutes‐selectivity to facilitate enhanced industrial uptake. Herein, we describe the use of two 2, 2′‐biphenol (BIPOL) derivatives to fabricate hyper‐crosslinked, microporous polymer nanofilms through IP. Ultra‐thin, defect‐free polyesteramide/polyester nanofilms (≈5 nm) could be obtained readily due to the relatively large molecular size and ionized nature of the BIPOL monomers retarding the rate of the IP. The enhanced microporosity arises from the hyper‐crosslinked network structure and monomer rigidity. Specifically, the amino‐BIPOL/PAN membrane exhibits extraordinary permselectivity performances with molecular weight cut‐off as low as 233 Da and MeOH permeance of ≈13 LMH/bar. Precise separation of small dye mixtures with similar M.W. based on both their charge and molecular size are achieved. Abstract : Ultra‐thin microporous polymer composite membranes with extraordinary perm‐selectivity for organic solvent nanofiltration were fabricated by employing two novel 2, 2′‐biphenol (BIPOL) derivatives as IP monomers. The enhanced microporosity arises from the hyper‐crosslinked network structure and monomer rigidity. Moreover, it can achieve precise separation of organic molecules with similar molecular weights on their charge and molecular size.